1985
DOI: 10.1017/s0022112085003457
|View full text |Cite
|
Sign up to set email alerts
|

On the deformation and drag of a type-A multiple drop at low Reynolds number

Abstract: The dynamics of a perfectly symmetric type-A multiple drop is studied. Up to first order in Reynolds number a force balance predicts the size ratios of the two constituents of such a drop to be unique for each system. Inertial effects are shown (a) to be destabilizing and (b) to exclude the possibility of obtaining perfectly concentric type-A droplets in a diffusion column. This latter conclusion is strengthened further by the sedimentation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…(20)- (24). First, in the limit of a very thin shell (λ → 1) or a very viscous shell (μ 23 → ∞), the velocity field vanishes.…”
Section: B Fluid Flow Equations and Their Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(20)- (24). First, in the limit of a very thin shell (λ → 1) or a very viscous shell (μ 23 → ∞), the velocity field vanishes.…”
Section: B Fluid Flow Equations and Their Solutionsmentioning
confidence: 99%
“…Inertia correction to the solution of Ref. [23] was made by Brunn and Roden [24], who found that the drop will deform in creeping flow, in contrast to the solution for simple drops that asserts the drop remains spherical, regardless of the capillary number [25]. The authors showed that the fluid flow tends to elongate the inner drop in the direction of the gravity, while it elongates the outer drop in the perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to Brunn and Roden (1985), these authors also obtained a linearized result (small Re) for shell deformation-again under the same, rather stringent assumption that the core remains at the center of the shell. They then, in a sense, generalized the Taylor-Acrivos results for a simple droplet to a (concentric) compound droplet.…”
Section: Compound Drop In Free-fallmentioning
confidence: 94%
“…On the assumption that the core is concentric and thus motionless (no translation) relative to the shell, Brunn and Roden (1985) obtained the potentially important result that both core and shell are still perfect spheres (for droplets at their terminal velocity and Re = 0)-a result that, like the simple drop, even holds true for yC and yS + 0.…”
Section: Dropmentioning
confidence: 99%
“…Fluid mechanics of such multiple emulsion drops or bubbles has been discussed extensively by Johnson and Sadhal 7 and Sadhal et al 8 Although a number of works deserve to be referred to as a basis of the present study, we restrict our attention here to the related problem of a concentric double emulsion droplet. Rushton and Davies 9 studied the translation of a concentric spherical double emulsion drop in an infinite fluid and Brunn and Roden 10 extended their work to consider the inertia correction to the translating drop. The most interesting result of these analyses is that the drop deforms at zero Reynolds numbers, unlike a single translating drop, which remains spherical at zero Reynolds number independently of the magnitude of capillary number.…”
Section: Introductionmentioning
confidence: 99%